Impact of caloric restriction on the Wnt/β-catenin pathway in the hippocampus and cortex of a Kindled rat model - Uribe, Eric; López-Landa, Alejandro; Serrano-García, Norma; Ochoa, Ernesto; Marin-Castañeda, Luis A.; Vázquez, David; Orozco, Sandra; Romo-Parra, Héctor; Gonzalez-Garibay, Guillermo; Rubio-Osornio, Moisés; Rubio, Carmen (European Journal of Clinical and Experimental Medicine, 2025)
Introduction and aim. Epilepsy is a common neurological disorder, and despite numerous treatment options, approximately 30% of patients have drug-resistant epilepsy. This situation prompts the exploration of alternative treatments such as caloric restriction (CR), whose mechanisms of antiepileptic action need to be fully elucidated. One of the key overactivated pathways in epilepsy is the Wnt/β-catenin pathway. Material and methods. To explore the potential regulatory effects of CR on this pathway, we conducted a study using twenty-eight male Wistar rats divided into four groups (7 animals each): Control, Sham (20% CR), kindling ad libitum (KAL), and kindling with CR (KCR). Caloric restriction rats received 80% of their daily food intake based on body weight, compared to those fed ad libitum. The kindling model was achieved by the introduction of an electrode in the basolateral nucleus of the amygdala. Immunofluorescence and Western blot techniques were used for the analysis of protein levels (Wnt, β-catenin, GSK3β, and cyclin D) in the frontal cortex and hippocampus. Results. Electroencephalographically and behaviorally, the KCR group exhibited a shorter duration of seizures and an increased behavioral threshold compared to the KAL group. Protein analysis revealed an increase in Wnt pathway proteins (Wnt, β-catenin, and cyclin D) in the KAL group compared to the control group. In contrast, CR reduced protein levels in animals that were induced to kindling. Conclusion. These findings suggest that CR may exert its antiepileptic effects through the regulation of the Wnt pathway by inhibiting its activity in the hippocampus and cortex of kindled rats.